Sex differences in health and disease: A review of biological sex differences relevant to cancer with a spotlight on glioma - Massey, Susan Christine; Whitmire, Paula; Doyle, Tatum E.; Ippolito, Joseph E.; Mrugala, Maciej M.; Hu, Leland S.; Canoll, Peter; Anderson, Alexander R.A.; Wilson, Melissa A.; Fitzpatrick, Susan M.; McCarthy, Margaret M.; Rubin, Joshua B.; et al. (Cancer letters, 2021)
The influence of biological sex differences on human health and disease, while being increasingly recognized, has long been underappreciated and underexplored. While humans of all sexes are more alike than different, there is evidence for sex differences in the most basic aspects of human biology and these differences have consequences for the etiology and pathophysiology of many diseases. In a disease like cancer, these consequences manifest in the sex biases in incidence and outcome of many cancer types. The ability to deliver precise, targeted therapies to complex cancer cases is limited by our current understanding of the underlying sex differences. Gaining a better understanding of the implications and interplay of sex differences in diseases like cancer will thus be informative for clinical practice and biological research. Here we review the evidence for a broad array of biological sex differences in humans and discuss how these differences may relate to observed sex differences in various diseases, including many cancers and specifically glioblastoma. We focus on areas of human biology that play vital roles in healthy and disease states, including metabolism, development, hormones, and the immune system, and emphasize that the intersection of sex differences in these areas should not go overlooked. We further propose that mathematical approaches can be useful for exploring the extent to which sex differences affect disease outcomes and accounting for those in the development of therapeutic strategies. •Biological sex differences appear in many aspects of normal human biology•Sex differences may influence the etiology of many diseases—more work is needed•Immune, metabolic, & genetic sex differences affect glioblastoma treatment outcomes•Patients may benefit from sex–specific therapeutic strategies•Computational models can elucidate molecular sex–difference impacts on disease